Soft magnetic metal powder, magnetic core, magnetic component, and electronic device
Patent Information
- Application Number
- CN202610520416.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-21
- Filing Date
- 2026-04-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]发明所要解决的技术问题
Smart Images

Figure CN122968084A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to soft magnetic metal powder, magnetic core, magnetic components, and electronic devices. Background Technology
[0002] Patent Document 1 describes a magnetic core using a composite magnetic material, which is obtained by mixing iron-based crystalline alloy magnetic powder and iron-based amorphous alloy magnetic powder to obtain a mixed magnetic powder, and further mixing an insulating binder material therein.
[0003] Patent document 2 describes an inductor using a composite magnetic material, which is obtained by mixing Fe-Ni alloy magnetic powder with hard amorphous alloy magnetic powder to obtain a mixed magnetic powder, and then coating each particle contained therein with a thermosetting resin.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-197218
[0007] Patent Document 2: Japanese Patent Application Publication No. 2004-363466 Summary of the Invention
[0008] The technical problem that the invention aims to solve
[0009] The purpose of this invention is to provide a soft magnetic metal powder with high voltage resistance and small voltage resistance deviation.
[0010] Technical solutions for solving technical problems
[0011] To achieve the above objectives, the soft magnetic metal powder of the present invention comprises soft magnetic metal particles having a core and a coating portion, wherein the coating portion has a carbon-rich portion with a higher C concentration than the core portion.
[0012] The aforementioned coating portion may have an oxide portion that is in contact with the surface of the aforementioned core portion.
[0013] It could be that, based on the atomic number, the maximum concentration of C in the aforementioned carbon-enriched portion (C(LM)) is more than 10 times the concentration of C (C(P)) in the aforementioned soft magnetic metal powder.
[0014] The thickness of the aforementioned carbon-enriched portion can be greater than 0.5 nm and less than 50.0 nm.
[0015] The aforementioned covering portion may have a coating portion that contacts the surface of the aforementioned carbon-enriched portion.
[0016] The magnetic core of the present invention comprises the above-mentioned soft magnetic metal powder.
[0017] The magnetic component of the present invention comprises the aforementioned soft magnetic metal powder.
[0018] The electronic device of the present invention comprises the above-described soft magnetic metal powder. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the cross-section of a soft magnetic metal particle.
[0020] Figure 2 This is an example of a chart obtained through X-ray crystal structure analysis.
[0021] Figure 3 In order to pass through Figure 2 An example of a pattern obtained by contour fitting of a chart.
[0022] Figure 4 This is a schematic diagram of a Weibull plot.
[0023] Figure 5 This is a cross-sectional schematic diagram of the powder coating device. Detailed Implementation
[0024] Hereinafter, the soft magnetic metal powder and the like according to embodiments of the present invention will be described.
[0025] The magnetic core of this embodiment contains soft magnetic metal powder as a magnetic material.
[0026] Furthermore, the magnetic core may contain resin. There are no particular restrictions on the type and content of the resin. Examples of resin types include thermosetting resins such as phenolic resin and epoxy resin. The resin content relative to the magnetic powder can be more than 1% by mass and less than 5% by mass.
[0027] exist Figure 1 The diagram shows a cross-sectional view of the soft magnetic metal particles 1 contained in the soft magnetic metal powder. (See diagram below.) Figure 1 As shown, the soft magnetic metal particle 1 has a core portion 2 and a coating portion 10.
[0028] (Core Part 2)
[0029] There are no particular restrictions on the composition of the core 2, as long as it is composed of a soft magnetic metal. For example, the core 2 can be an iron-based soft magnetic metal, wherein the total amount of Fe, Co, and Ni is 75 at% or more, and the proportion of Fe relative to the total amount of Fe, Co, and Ni is 50 at% or more. Furthermore, by making the proportion of Co relative to the total amount of Fe, Co, and Ni in the core 2 between 1 at% and 50 at% it is easy to have a carbon-rich portion in the coating portion 10, which facilitates the fabrication of a magnetic core with a large m value and small voltage tolerance deviation, as described later.
[0030] By making the core 2 a soft magnetic iron metal, it is easy to reduce the coercivity Hc of the magnetic core and further increase the relative permeability of the magnetic core.
[0031] Typically, the core 2 is significantly larger than the coating 10. In fact, the composition of the soft magnetic metal powder, the soft magnetic metal particles 1, and the core 2 can be considered to be completely identical.
[0032] There are no particular restrictions on the composition of soft magnetic metal powders. For example, compositions that readily exhibit amorphous structures can be listed, such as Fe-Co-B-P-Si-Cr, Fe-Si-B, Fe-Si-B-C, Fe-Si-B-C-Cr, Fe-Co-P-C, Fe-Co-B, and Fe-Co-B-Si systems. Furthermore, compositions that readily exhibit nanocrystalline structures can be listed, such as Fe-Si-B-Nb-Cu, Fe-Si-B-Nb-P, Fe-Co-B-P-Si, and Fe-Co-B-P-Si-Cr systems. Compositions that readily exhibit crystalline structures can also be listed, such as Fe-Si, Fe, Fe-Ni, Fe-Si-Cr, Fe-Si-Al, Fe-Si-Al-Ni, Fe-Ni-Si-Co, Fe-Co, Fe-Co-V, Fe-Co-Si, and Fe-Co-Si-Al systems.
[0033] The soft magnetic metal particle 1 can have the following composition, namely, in terms of atomic ratio, it consists of the following formula: constitute,
[0034] X1 is selected from one or more of Co and Ni.
[0035] X2 is selected from one or more of the following elements: Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O, and rare earth elements.
[0036] M is selected from one or more of Nb, Hf, Zr, Ta, Mo, W, Ti, and V.
[0037] 0≤a≤0.150,
[0038] 0≤b≤0.200,
[0039] 0≤c≤0.200,
[0040] 0≤d≤0.200,
[0041] 0≤e≤0.200,
[0042] 0≤f≤0.0200,
[0043] α≥0,
[0044] β≥0,
[0045] 0≤α+β≤0.50.
[0046] With a composition within the above range, the coercivity of the magnetic core is easily reduced, and the relative permeability of the magnetic core is easily increased.
[0047] Furthermore, it can be 0.100≤a+b+c+d+e≤0.300. By having a composition within the above range, and also satisfying 0.100≤a+b+c+d+e≤0.300, it is easy to form a structure composed of amorphous materials or nanocrystals, the coercivity is further easily reduced, and the relative permeability of the magnetic core is easily increased.
[0048] The soft magnetic metal particles 1 (core 2) may also contain elements other than those mentioned above (i.e., elements other than Fe, X1, X2, M, B, P, Si, C, and S) as unavoidable impurities. For example, they may contain less than 0.1% by mass of unavoidable impurities.
[0049] There are no particular restrictions on the microstructure of the core 2. It can be a structure composed of amorphous materials, nanocrystals, or crystals.
[0050] The term "structure composed of amorphous materials" refers to a structure with an amorphization rate (X) of 85% or higher. Structures containing crystals within an amorphization rate of 85% or higher are considered amorphous structures. Amorphous structures include structures composed almost entirely of amorphous materials or structures composed of heteroamorphous materials. "Structures composed of heteroamorphous materials" refers to structures containing crystals within amorphous materials. In the case of heteroamorphous structures, the average crystal grain size of the crystals present in the amorphous material can be 0.1 nm or more and 10 nm or less. "Structures composed of nanocrystals" refers to structures with an amorphization rate (X) of less than 85% and an average crystal grain size of less than 100 nm. The average crystal grain size of the crystals in a nanocrystal structure can be 3 nm or more and 50 nm or less. "Structures composed of crystals" refers to structures with an amorphization rate (X) of less than 85% and an average crystal grain size of greater than 100 nm.
[0051] The amorphization rate X can be determined by X-ray crystal structure analysis using XRD, or by EBSD (electron orientation resolution) or electron beam diffraction. The method for determining it using XRD is described below.
[0052] The amorphization rate X of soft magnetic metal powder is represented by the following formula (1).
[0053]
[0054] Ic: Crystal scattering integral intensity.
[0055] Ia: Integral intensity of amorphous scattering.
[0056] Regarding the amorphization rate X, X-ray crystal structure analysis of soft magnetic metal powder is performed by XRD, and the phase is determined. The peak values of crystallized Fe or compounds (Ic: crystal scattering integral intensity, Ia: amorphous scattering integral intensity) are read, and the crystallization rate is obtained based on the peak intensity. The calculation is then performed using the above formula (1). The calculation method is explained in more detail below.
[0057] X-ray crystal structure analysis of soft magnetic metal powder was performed using XRD to obtain the following results: Figure 2 The graph shown is used. The contour is fitted using the Lorentz function of equation (2) below, resulting in the graph shown below. Figure 3 The crystal composition pattern α shown represents the integrated intensity of crystal scattering. c α represents the amorphous composition pattern representing the integral intensity of amorphous scattering. a and the pattern α that combines them c+aThe amorphization rate X is obtained by using equation (1) above, based on the integrated intensity of crystalline and amorphous scattering of the obtained pattern. Furthermore, the measurement range is set to the range where the diffraction angle 2θ = 30° to 60° from the amorphous halo can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is kept within 1%.
[0058]
[0059] Where h: peak height, u: peak position, w: half-peak width, b: background height.
[0060] There are no particular limitations on the average particle size of the soft magnetic metal powder 1; for example, it can be greater than 1 μm and less than 50 μm. When using soft magnetic metal powder 1 with a small average particle size, the withstand voltage can be increased more easily, and the deviation in withstand voltage can also be reduced more easily. On the other hand, when the filling ratio of the magnetic core is the same, the smaller the average particle size of the soft magnetic metal powder 1, the easier it is to reduce the relative permeability of the magnetic core.
[0061] There are no particular limitations on the method for measuring the thickness of each part of the soft magnetic metal particle 1. For example, it can be measured by observing the cross-section of the soft magnetic metal particle 1 using various electron microscopes. Furthermore, when calculating the average thickness of each part in a soft magnetic metal powder containing multiple soft magnetic metal particles, the thickness of each part of at least 10 soft magnetic metal particles can be measured and averaged.
[0062] (Covering part 10)
[0063] The soft magnetic metal particle 1 in this embodiment has a coating portion 10 that contacts the surface of the core portion 2. For example... Figure 1 As shown, the coating portion 10 has multiple layers. The coating portion 10 has at least a carbon-enriched portion 12. The carbon-enriched portion 12 refers to a layer where the C concentration is higher than that of the core portion 2. The value obtained by subtracting the C concentration (at%) of the core portion 2 from the C concentration (at%) of the carbon-enriched portion 12 can be 0.1 or more, or 0.5 or more. There is no particular limitation on the thickness of the carbon-enriched portion 12; for example, it can be 0.5 nm or more and 50.0 nm or less, preferably 0.5 nm or more and 10.0 nm or less, and more preferably 0.5 nm or more and 3.0 nm or less.
[0064] The average thickness of the carbon enrichment portion 12 in a soft magnetic metal particle 1 can be 0.5 nm or more and 50.0 nm or less, preferably 0.5 nm or more and 10.0 nm or less, and more preferably 0.5 nm or more and 3.0 nm or less.
[0065] The average thickness of the carbon enrichment portion 12 in the soft magnetic metal powder having multiple soft magnetic metal particles 1 can be 0.5 nm or more and 50.0 nm or less, preferably 0.5 nm or more and 10.0 nm or less, and more preferably 0.5 nm or more and 3.0 nm or less.
[0066] By incorporating a carbon-enriched portion 12 into the coating portion 10 of the soft magnetic metal particles 1, deviations in withstand voltage in magnetic cores made from soft magnetic metal powder containing the soft magnetic metal particles 1 can be suppressed. The details of the reasoning behind suppressing withstand voltage deviations in the magnetic core by incorporating the soft magnetic metal powder with the aforementioned configuration are not clear. However, the reasoning is believed to be as follows: by incorporating the soft magnetic metal powder with the aforementioned configuration, the compressibility of the soft magnetic metal powder can be reduced and its flowability improved, thereby suppressing withstand voltage deviations in the magnetic core.
[0067] There is no particular limitation on the proportion of soft magnetic metal particles with carbon-enriched portions 12 relative to all soft magnetic metal particles contained in the soft magnetic metal powder. This proportion only needs to be at least 1% by mass. Furthermore, there is no particular limitation on the proportion of soft magnetic metal particles with carbon-enriched portions 12 in the magnetic core containing the soft magnetic metal powder. For example, when the magnetic core containing the soft magnetic metal powder is cut at any cross-section, it is acceptable as long as there is one or more particles containing carbon-enriched portions 12.
[0068] The thickness of the carbon-enriched portion 12 contained in a single soft magnetic metal particle 1 does not need to be uniform. That is, the thickness of the carbon-enriched portion 12 may be biased or deviated. In addition, there may be localized areas where no carbon-enriched portion 12 is formed. It is sufficient as long as the carbon-enriched portion 12 directly or indirectly covers more than 50% of the surface of the core portion 2. However, the thickness of the carbon-enriched portion 12 contained in a single soft magnetic metal particle 1 is preferably as uniform as possible.
[0069] For example, in the cross-section of a single soft magnetic metal particle 1, the arithmetic mean height Ra of the rim curve of the surface of the carbon-enriched portion 12 is preferably 0.5 nm or more and 100 nm or less. Ra can be calculated according to, for example, the method specified in JIS specification B601.
[0070] For a soft magnetic metal powder or magnetic core containing multiple soft magnetic metal particles 1, the Ra of at least 10 soft magnetic metal particles 1 is calculated and averaged. Thus, the Ra of the soft magnetic metal powder or magnetic core can be calculated.
[0071] There are no particular restrictions on the evaluation method for withstand voltage deviation. The following is an example of an evaluation method using the Weibull distribution.
[0072] According to the Weibull distribution, the failure rate λ(t) with respect to time t is represented by the following equation (I). Here, m is called the Weibull coefficient, and α is called the scaling parameter.
[0073]
[0074] When m < 1, equation (I) represents the property that the failure rate decreases with time. When m = 1, equation (I) represents the property that the failure rate is constant with respect to time. When m > 1, equation (I) represents the property that the failure rate increases with time. The following explains how to calculate the Weibull coefficient m.
[0075] The following equation (II) represents the reliability (probability of no failure) R(t) of a product with the above failure rate λ(t).
[0076]
[0077] Furthermore, the unreliability (cumulative failure rate) F(t) is represented by the following equation (III).
[0078]
[0079] Transforming equation (III) yields equation (IV).
[0080]
[0081] Among them, let When x = lnt, we get the following equation (V).
[0082]
[0083] That is, plotting relative to x = lnt If we obtain a straight line, we can calculate the Weibull coefficient m based on its slope. This method is called the Weibull plot method.
[0084] When m > 1, the larger the Weibull coefficient m, the more rapidly the unreliability (cumulative failure rate) F(t) increases near a certain time t. That is, the larger the Weibull coefficient m, the smaller the deviation in the time before each product fails.
[0085] A schematic diagram of the Weibull diagram is shown below. Figure 4 .exist Figure 4 In the Weibull diagram, compared to when m = 1.5, when m = 3, F(t) increases sharply around a certain time t. That is, when m is large, multiple products fail simultaneously around a certain time t, and the deviation in the time before each product fails is small. Furthermore, in the Weibull diagram, the further the line moves to the right, the longer the time before each product fails.
[0086] The withstand voltage of multiple magnetic cores is measured, and the results are plotted on a Weibull plot, from which the Weibull coefficient *m* can be determined. Withstand voltage refers to the applied voltage when a voltage is applied to the magnetic core while a specified current flows through it. Furthermore, the aforementioned "time *t*" can be replaced with "applied voltage *V* per unit length," and the aforementioned "fault" can be replaced with "current flowing through it," thus enabling the Weibull plotting. There are no particular limitations on the method of Weibull plotting. Besides calculating *m* by plotting experimental results on Weibull probability paper, computer programs that automatically plot Weibull figures and calculate the Weibull coefficient *m* when experimental results are input have become widely used in recent years.
[0087] As mentioned above, when evaluating the withstand voltage deviation using the Weibull distribution, the larger the Weibull coefficient m, the smaller the withstand voltage deviation.
[0088] Based on atomic number, the maximum concentration of C in the carbon-enriched section 12 (C(LM)) can be more than 10 times the concentration of C (C(P)) in the soft magnetic metal powder. By increasing the maximum concentration of C in the carbon-enriched section 12, it is easier to reduce the deviation in withstand voltage. There are no particular restrictions on the method for calculating the maximum concentration of C. For example, it can be calculated by observing the cross-section of the soft magnetic metal particle 1 using STEM-EDS or the like. In addition, this maximum value can also be called the maximum value.
[0089] The types and concentrations of components contained in various parts of soft magnetic metal particles, such as soft magnetic metal particles and carbon-enriched regions, can be determined, for example, based on information obtained by elemental analysis using energy dispersive X-ray spectroscopy (EDS) such as scanning transmission electron microscopy (STEM) or elemental analysis using electron energy loss spectroscopy (EELS) such as STEM.
[0090] The composition of the soft magnetic metal particles 1 can also be analyzed using 3DAP (three-dimensional atomic probe microanalysis). When using 3DAP, a small region (e.g., a region of Φ20nm × 100nm) containing the carbon-rich portion 12 can be defined inside the soft magnetic metal particle being measured, and the average composition of the carbon-rich portion 12 can be determined. That is, when the soft magnetic metal particles are contained within a magnetic core, the influence of the resin components contained in the magnetic core and the oxidation of the surface of the soft magnetic metal particles can be excluded to determine the composition of the soft magnetic metal particle body.
[0091] The concentration distribution of each element near the surface of the soft magnetic metal particle 1 can be measured, for example, using STEM and EDS along a direction perpendicular to the outermost surface of the soft magnetic metal particle 1. Furthermore, by plotting the results on a graph, the maximum concentration of C can be determined. Moreover, there is no particular limitation on the number of observation sites within a single soft magnetic metal particle 1. There can be one or more observation sites within a single soft magnetic metal particle 1. Furthermore, there is no particular limitation on the number of soft magnetic metal particles observed. For example, more than five soft magnetic metal particles can be randomly selected from the soft magnetic metal powder for observation, or more than 20 soft magnetic metal particles can be randomly selected for observation.
[0092] The position of the oxide portion 11 included in the coating portion 10 can be determined based on the concentration of O in the soft magnetic metal particles 1 and the concentration of O in the coating portion 10. For example, firstly, the average concentration of O in the soft magnetic metal particles 1 is calculated. Then, the region near the surface of the soft magnetic metal particles 1 in the coating portion 10 where the O concentration is higher than the average O concentration in the soft magnetic metal particles 1 can be considered as the oxide portion 11.
[0093] There are no particular limitations on the method for determining the composition of the carbon-enriched portion 12. For example, analysis can be performed using an EDX device or EPMA attached to an electron microscope.
[0094] In this embodiment, the coating portion 10 of the soft magnetic metal particle 1 may have an oxide portion 11 in contact with the surface of the core portion 2, in addition to the carbon enrichment portion 12. When the soft magnetic metal particle 1 has an oxide portion 11, the withstand voltage can be further improved, and the deviation of the withstand voltage can be further reduced.
[0095] There are no particular restrictions on the composition of the oxide portion 11. For example, the oxide portion 11 may contain an oxide of the element contained in the core portion 2. This oxide may be a simple oxide or a complex oxide.
[0096] There are no particular limitations on the thickness of the oxide portion 11; for example, it can be 0.5 nm or more and 200 nm or less.
[0097] The average thickness of the oxide portion 11 in a soft magnetic metal particle 1 can be 0.5 nm or more and 200 nm or less.
[0098] The average thickness of the oxide portion 11 in the soft magnetic metal powder having multiple soft magnetic metal particles 1 can be 0.5 nm or more and 200 nm or less.
[0099] The thickness of the oxide portion 11 contained in a single soft magnetic metal particle 1 does not need to be uniform. That is, the thickness of the oxide portion 11 may be biased or deviated. In addition, there may be localized areas where no oxide portion 11 is formed. The oxide portion 11 may cover more than 50% of the surface of the core portion 2. However, the thickness of the oxide portion 11 contained in a single soft magnetic metal particle 1 is preferably as uniform as possible.
[0100] In this embodiment, the coating portion 10 of the soft magnetic metal particle 1 may have a coating portion 13 in contact with the surface of the carbon enrichment portion 12, in addition to the carbon enrichment portion 12. There are no particular limitations on the composition of the coating portion 13. For example, the coating portion 13 may be formed by glass coating, a process commonly practiced in this art. For example, the coating portion 13 may contain phosphate glass or silica glass.
[0101] When the soft magnetic metal particle 1 has a coating portion 13, the withstand voltage can be further improved and the deviation of the withstand voltage can be further reduced.
[0102] The thickness of the coating portion 13 contained in a single soft magnetic metal particle 1 does not need to be uniform. That is, the thickness of the coating portion 13 may be biased or deviated. In addition, there may be localized areas where no coating portion 13 is formed. The coating portion 13 may directly or indirectly cover more than 50% of the surface of the core portion 2. However, the thickness of the coating portion 13 contained in a single soft magnetic metal particle 1 is preferably as uniform as possible.
[0103] The carbon enrichment portion 12 is conductive. Nevertheless, for a magnetic core made using soft magnetic metal powder containing soft magnetic metal particles 1 with carbon enrichment portion 12, the withstand voltage is not reduced compared to a magnetic core made using soft magnetic metal powder without soft magnetic metal particles 1 with carbon enrichment portion 12, and the deviation in withstand voltage is smaller.
[0104] When the soft magnetic metal particles 1 have carbon-enriched portions 12 on their outermost sides, the flowability of the soft magnetic metal powder containing the soft magnetic metal particles 1 with carbon-enriched portions 12 is relatively improved. Therefore, when pressure is applied during the fabrication of the magnetic core, the soft magnetic metal particles 1 move more easily. At the same time, the surface condition of the soft magnetic metal particles 1 can be improved, preventing localized electric field concentration. Thus, it is achieved that the voltage withstand deviation is reduced without decreasing the voltage withstand capability.
[0105] Furthermore, even when the soft magnetic metal particles 1 have a coating portion 13 on the outside of the carbon enrichment portion 12, the flowability of the soft magnetic metal powder, including the soft magnetic metal particles 1 before the coating portion 13 is formed, is improved due to the carbon on the surface of the soft magnetic metal particles 1 in the stage before the coating portion 13 is formed. Therefore, the coating portion 13 can be formed more uniformly. As a result, the voltage withstand deviation is reduced.
[0106] The following describes the method for manufacturing the soft magnetic metal powder according to this embodiment.
[0107] First, prepare a soft magnetic metal powder containing soft magnetic metal particles, which will ultimately form the core 2. There are no particular restrictions on the method for preparing the soft magnetic metal powder. For example, commercially available soft magnetic metal powder can be prepared, or it can be produced by atomization methods such as water atomization or gas atomization.
[0108] Whether the soft magnetic metal powder obtained by atomization has an amorphous or crystalline structure is mainly determined by the composition of the soft magnetic metal powder.
[0109] When soft magnetic metal powder obtained by atomization has an amorphous structure, heat treatment can sometimes precipitate nanocrystals with a particle size of 5 nm to 50 nm, resulting in soft magnetic metal powder with a nanocrystal structure. Whether nanocrystals can be precipitated by heat treatment is mainly determined by the composition of the soft magnetic metal powder.
[0110] Regarding heat treatment conditions, for example, the temperature should be above 350°C and below 800°C for at least 1 minute and less than 300 minutes. Furthermore, typically, a single soft magnetic metal particle contains multiple nanocrystals. That is, the particle size of the soft magnetic metal particle is different from the crystal size of the nanocrystals. Moreover, the crystal structure of the soft magnetic metal powder can be confirmed using XRD or transmission electron microscopy. When the soft magnetic metal powder contains nanocrystals, the final magnetic core's Hc is more likely to decrease, and its relative permeability is more likely to increase.
[0111] The average particle size of soft magnetic metal powder can be adjusted by changing the atomization conditions. Alternatively, it can be adjusted by grading. Furthermore, the average particle size can be adjusted by blending multiple soft magnetic metal powders with different average particle sizes.
[0112] Next, a coating portion of the soft magnetic metal particles contained in the soft magnetic metal powder is made.
[0113] There are no particular restrictions on the method used to fabricate the oxide layer on the surface of the core. For example, the surface of the soft magnetic metal particles can be oxidized by heat treatment in an oxygen-containing atmosphere. There are no particular restrictions on the oxygen concentration in the atmosphere; for example, it can be from 1 ppm to 20,000 ppm. There are no particular restrictions on the heat treatment temperature; for example, it can be from 150°C to 800°C. There are no particular restrictions on the heat treatment time; for example, it can be from 0.1 hours to 10 hours. The higher the oxygen concentration, the higher the heat treatment temperature, and the longer the heat treatment time, the easier it is to thicken the oxide layer.
[0114] The method for creating the carbon enrichment section is explained.
[0115] There are no particular restrictions on the methods used to create carbon-enriched sections. For example, it can be done by using... Figure 5 The powder coating apparatus 100 shown uses a mechanical alloying method to form a carbon-enriched section.
[0116] First, soft magnetic metal powder and carbon powder that form the carbon enrichment region are added to... Figure 5 In the powder coating apparatus 100 shown, a mixture 50 is obtained by mixing soft magnetic metal powder and carbon powder. By rotating the rotor 101 in this state, the mixture 50 is compressed between the pressure head 102 and the inner wall of the rotor 101, generating heat through friction. Due to this frictional heat, the carbon powder softens, and due to the compression, the carbon is fixed on the surface of the core (or, in the case of an oxide section, on the surface of the oxide section), thus forming a carbon-enriched section.
[0117] There are no particular limitations on the average particle size of the carbon powder. The average particle size of the carbon powder can be set to approximately one-tenth or less of the average particle size of the soft magnetic metal powder. There are no particular limitations on the atmosphere in the powder coating apparatus 100. For example, an inert atmosphere (e.g., Ar atmosphere) can be used. Furthermore, the oxygen concentration in the atmosphere can be set to 1–20,000 ppm. There are no particular limitations on the amount of carbon powder added. For example, the amount of carbon powder added relative to 100 parts by mass of the soft magnetic metal powder can be 0.01–10 parts by mass. The more carbon powder added, the easier it is to increase the thickness of the carbon-enriched portion. There are no particular limitations on the coating time; for example, it can be 0.5–10 hours. There are no particular limitations on the temperature of the mixture.
[0118] Next, there are no particular restrictions on the coating method used when making the coating part, and methods commonly used in this technical field can be adopted.
[0119] For example, dry coating can be performed. There are no particular restrictions on the type of coating at this time. For example, a coating made of phosphate-based glass can be formed. In this case, the powder coating apparatus 100 described above can be used to mix phosphate-based glass powder with the soft magnetic metal powder in which the carbon enrichment part has been formed to make mixture 50.
[0120] For example, wet coating can also be performed. There are no particular restrictions on the type of coating at this time. For example, a coating composed of Si oxide can be produced by using the sol-gel method of TEOS.
[0121] Since the powder flowability is improved by forming the carbon enrichment portion 12, the coating portion 13 can easily become uniform.
[0122] There are no particular restrictions on the magnetic powder used in the fabrication of the magnetic core. The aforementioned soft magnetic metal powder can be used directly as the magnetic powder, or it can be mixed with other powders to create the magnetic powder.
[0123] The obtained magnetic powder is then molded to obtain a magnetic core. There are no particular limitations on the molding method. As an example, a method for obtaining a magnetic core by pressure molding will be described.
[0124] First, the magnetic powder is mixed with the resin. By mixing the resin, a high-strength molded body can be easily obtained through molding. There are no particular restrictions on the type of resin. For example, phenolic resin and epoxy resin can be used. There are also no particular restrictions on the amount of resin added. When adding resin, it can be added at more than 1% by mass and less than 5% by mass relative to the magnetic powder.
[0125] Granulated powder is obtained by granulating a mixture of magnetic powder and resin. There are no particular limitations on the granulation method. For example, a stirrer can be used for granulation. There are no particular limitations on the particle size of the granulated powder.
[0126] The obtained granulated powder is pressurized to form a molded body. There are no particular limitations on the molding pressure; for example, it can be set to a surface pressure of 0.1 ton / cm². 2 Above and 10 tons / cm 2 The higher the molding pressure, the easier it is to increase the relative permeability. However, when the particle size distribution of the magnetic powder is wide, the relative permeability can still be improved even when the molding pressure is set lower than that used in normal pressure molding. This is because the resulting magnetic core is more likely to become dense.
[0127] Then, the resin contained in the molded body is cured to obtain a magnetic core. There are no particular restrictions on the curing method; heat treatment can be performed under conditions that allow the resin used to cure.
[0128] There are no particular limitations on the application of the magnetic core. For example, it is suitable for use as a magnetic core for inductors, especially for power inductors. Moreover, it is also suitable for use in inductors in which the magnetic core and coil are integrally formed.
[0129] Furthermore, the aforementioned magnetic core or magnetic components using the aforementioned magnetic core can be well applied to electronic devices.
[0130] In particular, because the aforementioned magnetic cores have high voltage withstand capability and small voltage tolerance deviation, they are suitable for applications requiring miniaturization, lightweight design, and high reliability. For example, they are suitable for use in magnetic cores, magnetic components, and electronic devices in hybrid electric vehicles, plug-in hybrid electric vehicles, and electric vehicles.
[0131] Example
[0132] The present invention will now be described in detail based on specific embodiments.
[0133] (Experimental Example 1)
[0134] Soft magnetic metal powders with compositions shown in the "Core Composition" column of Table 1 are prepared. Specifically, ingots of various materials are prepared as raw material metals to obtain molten metal with the target composition, and weighed. Then, after evacuating the chamber, the crucible is heated by high-frequency induction using a working coil located outside the crucible to melt and mix the raw material metals in the crucible, obtaining molten metal (molten liquid) at 1400°C to 1600°C.
[0135] The obtained molten liquid is supplied to the chamber in a continuous, linear flow through a nozzle located at the bottom of the crucible. Gas is then blown onto the supplied molten liquid to obtain powder. The gas injection temperature is set to 20°C.
[0136] In samples 5 and 6, the obtained powders were heat-treated at 550°C for 60 minutes in an inert atmosphere.
[0137] The obtained powder was classified using a sieve. Through classification, the average particle size of the powder was reduced to approximately 25 μm.
[0138] ICP analysis confirmed that the composition of the molten metal was approximately consistent with that of the soft magnetic metal powder. Furthermore, the compositions of samples 1 and 2 were 88.0Fe–12.0Si; samples 3 and 4 were 72.7Fe–11.6Si–10.8B–2.2Cr–2.7C; and samples 5 and 6 were 73.5Fe–13.5Si–9.0B–3.0Nb–1.0Cu. In this embodiment, all compositions are described using atomic ratios.
[0139] The fine structure of each soft magnetic metal powder was confirmed by XRD. It was confirmed that: samples 1 and 2 have a crystalline structure; samples 3 and 4 have an amorphous structure; and samples 5 and 6 have a nanocrystalline structure. In the tables below, samples marked "crystalline" in the fine structure column have a crystalline structure. Samples marked "amorphous" have an amorphous structure. Samples marked "nanocrystalline" have a nanocrystalline structure.
[0140] Then, carbon enrichment zones are formed on the obtained powder. In addition, for powders with "0" marked in the column for the average thickness of the carbon enrichment zone, no carbon enrichment zone is formed.
[0141] To form carbon-rich areas on the surface of soft magnetic metal powder, carbon powder was added together with the soft magnetic metal powder. Figure 5 In the powder coating apparatus shown, the atmosphere in the powder coating apparatus is set to an inert atmosphere (Ar atmosphere). The average particle size of the carbon powder is made to be less than 1 / 10 of the average particle size of the soft magnetic metal powder. The amount of carbon powder added is appropriately controlled so that the average thickness of the carbon-enriched portion in the final soft magnetic metal powder is as shown in the respective tables. Specifically, the amount of carbon powder added is as follows: 0.1 to 3 parts by mass relative to 100 parts by mass of the soft magnetic metal powder. In addition, the coating time is 0.5 to 3 hours. And the average thickness of the carbon-enriched portion, measured by the measurement method described later, is as shown in Table 1.
[0142] In all embodiments, the concentration of C in the carbon-enriched portion was confirmed to be 80 at% or higher. Furthermore, in addition to C, the carbon-enriched portion sometimes also contains elements found in the core, such as oxygen. However, in all embodiments, it was confirmed that the concentration of C in the carbon-enriched portion was higher than the concentration of C in the core.
[0143] The thickness of the carbon-enriched portion of the soft magnetic metal particles contained in the soft magnetic metal powder was calculated by observing the cross-section of the soft magnetic metal particles using STEM. Furthermore, the average thickness of the carbon-enriched portion in the soft magnetic metal powders of each embodiment and comparative example was calculated by measuring the thickness of the carbon-enriched portion of at least 10 soft magnetic metal particles and taking the average value. Moreover, it was confirmed that the arithmetic mean height Ra of the carbon-enriched portion in all the soft magnetic metal particles contained in the soft magnetic metal powders of all embodiments was 0.5 nm or more and 100 nm or less.
[0144] Next, a cylindrical magnetic core was fabricated using the obtained soft magnetic metal powder.
[0145] Soft magnetic metal powder was mixed with resin (phenolic resin). The mixture was prepared at a resin content of 3% by mass. Next, granulation was performed using a standard planetary mixer to obtain granulated powder with a particle size of approximately 500 μm. The obtained granulated powder was then subjected to a surface pressure of 4 tons / cm². 2 Pressure molding is performed to obtain a cylindrical molded body with a diameter of 8.0 mmφ and a height of 8.0 mm. The obtained molded bodies are then cured at a temperature of 150°C to obtain a cylindrical magnetic core.
[0146] Twenty cylindrical magnetic cores were fabricated for each sample. In-Ga electrodes were formed on two faces of each cylindrical magnetic core perpendicular to the thickness direction. Next, a voltage was applied using a source meter (THK-2011ADMPT from Domo Electric Measurements), and the voltage was measured when a current of 10 mA flowed through it. The withstand voltage of the cylindrical magnetic core was then measured by dividing this voltage by the thickness of the cylindrical magnetic core. The average withstand voltage of the 20 cylindrical magnetic cores was taken as the withstand voltage of each sample. Furthermore, a Weibull plot was performed on the withstand voltage of the 20 cylindrical magnetic cores, and the m-value of each sample was calculated. An m-value of 4.0 or higher was considered good, and 5.5 or higher was even better.
[0147] Table 1
[0148]
[0149] As shown in Table 1, for soft magnetic metal powders with carbon-enriched coatings, both the withstand voltage and the m-value are improved compared to soft magnetic metal powders produced under the same conditions except for those without carbon-enriched coatings. The improvement in withstand voltage and m-value is due to the reduction in the areas where localized electric field concentration occurs, resulting from the formation of carbon-enriched coatings.
[0150] (Experimental Example 2)
[0151] Samples 2, 4, and 6 were subjected to the same treatment under the same conditions, except that an oxide layer was formed on the surface of the soft magnetic metal powder before the formation of the carbon-rich layer. Specifically, each soft magnetic metal powder was heat-treated for 1 hour at a temperature of 300°C and an oxygen concentration of 10–10000 ppm. The thickness of the oxide layer varied due to changes in oxygen concentration. The average thickness of the oxide layer in the soft magnetic metal powder after the above heat treatment was measured. The results are shown in Table 2.
[0152] Table 2
[0153]
[0154] As shown in Table 2, in the embodiments with oxide portions, the withstand voltage and m value are both improved compared to the embodiments implemented under the same conditions except for those without oxide portions.
[0155] (Experimental Example 3)
[0156] (Sample numbers 21-24)
[0157] For sample number 12, the procedure was performed under the same conditions, except that the oxygen concentration in the atmosphere of the powder coating apparatus was increased. Specifically, the oxygen concentration was varied within the range of 0–10000 ppm. Then, C(LM) was measured for each sample, and C(LM) / C(P) was calculated. The results are shown in Table 3.
[0158] (Sample numbers 25-28)
[0159] For samples numbered 12, 21-24, the composition of the soft magnetic metal powder was changed to 75.3Fe-11.6Si-10.8B-2.2Cr-0.1C, and the oxygen concentration in the powder coating device was controlled without changing C (LM). Otherwise, the process was carried out under the same conditions. The results are shown in Table 3.
[0160] Table 3
[0161]
[0162] The thickness of the carbon-enriched portion of the samples shown in Table 3 is 9–11 nm.
[0163] As shown in Table 3, in all embodiments where C(LM) / C(P) is 10 or more, the value of m is improved compared to embodiments where C(LM) / C(P) is less than 10.
[0164] In the experimental examples other than Experimental Example 3, the examples that were not specifically described were all examples in which C(LM) / C(P) was confirmed to be 10 or higher.
[0165] (Experimental Example 4)
[0166] For sample number 12, the average thickness of the carbon enrichment section was changed by varying the amount of carbon powder added to the powder coating device; otherwise, the procedure was performed under the same conditions. The results are shown in Table 4. Additionally, the results for samples 3 and 4 are also recorded for reference.
[0167] Table 4
[0168]
[0169] Table 4 shows that samples 12, 33-37, whose average carbon enrichment thickness varies from 0.5 nm to 50 nm, exhibit superior m values compared to samples 32 and 38, whose average carbon enrichment thickness is outside this range. Conversely, sample 31, which does not have a carbon enrichment, shows a lower m value.
[0170] (Experimental Example 5)
[0171] The soft magnetic metal powder shown in Table 5 before coating was coated to form a coated part, thereby producing samples numbered 41 to 58.
[0172] (Dry coating (phosphate coating))
[0173] Phosphate-based glass (P-Zn-Al-O oxide glass) was added together with soft magnetic metal powder. Figure 5 In the powder coating apparatus shown, the thickness of the coating is controlled to approximately 20 nm by controlling the amount of phosphate-based glass added, thus forming a coating composed of phosphate-based glass. The results are shown in Tables 5A to 5C.
[0174] (Wet coating (Si coating))
[0175] A coating consisting of Si oxides was formed on soft magnetic metal powder using the sol-gel method with TEOS. The thickness of the coating was controlled to approximately 20 nm by adjusting the concentration of TEOS. The results are shown in Tables 5A to 5C.
[0176] Table 5A
[0177]
[0178] Table 5B
[0179]
[0180] Table 5C
[0181]
[0182] In the embodiments where a coating portion is formed that contacts the surface of the carbon-rich portion, the withstand voltage is significantly improved compared to the embodiments implemented under the same conditions except that no coating portion is formed. Furthermore, in the case where the film (coating portion) is formed by dry coating, both the withstand voltage and the m value tend to be improved compared to the case where the film (coating portion) is formed by wet coating.
[0183] (Experimental Example 6)
[0184] For sample number 49, the experiment was conducted under the same conditions, except that the average particle size of the soft magnetic metal powder was varied. The results are shown in Table 6.
[0185] Table 6
[0186]
[0187] As shown in Table 6, the smaller the average particle size of the soft magnetic metal powder used, the better it can improve the withstand voltage and m value.
[0188] (Experimental Example 7)
[0189] The soft magnetic metal powder (without carbon enrichment) of sample number 3 and the soft magnetic metal powder (with carbon enrichment) of sample number 4 were mixed at the mixing ratio shown in Table 7, and a coating composed of phosphate was formed in the same manner as that for samples number 47 and 48. The results are shown in Table 7.
[0190] Table 7
[0191]
[0192] Table 7 confirms that as long as the soft magnetic metal powder contains at least a portion of soft magnetic metal particles with carbon enrichment relative to the overall soft magnetic metal powder, the m-value can be improved. It also confirms that the higher the proportion of soft magnetic metal particles with carbon enrichment, the greater the improvement in the m-value.
[0193] Furthermore, when using the powders listed in Table 7 to fabricate pressed magnetic cores, the presence or absence of carbon-enriched portions of each particle can be confirmed by observing the cross-section of the magnetic core using STEM-EDX. In other words, to determine the ratio of soft magnetic metal particles with carbon-enriched portions in the magnetic core, it is sufficient to determine the ratio of soft magnetic metal particles with carbon-enriched portions in the cross-section of the magnetic core.
[0194] (Experimental Example 8)
[0195] Except for altering the composition (core composition) of the soft magnetic metal powder, samples 81-100 were performed in the same manner as samples 1 and 2. In samples 81 and 82, the soft magnetic metal powder composition was essentially Fe-only. In samples 83 and 84, the atomic ratio was 55.0Fe–45.0Ni. In samples 85 and 86, the atomic ratio was 89.4Fe–8.6Si–2.0Cr. In samples 87 and 88, the atomic ratio was 73.7Fe–16.4Si–9.9Al. In samples 89 and 90, the atomic ratio was 78.1Fe–11.0Si–10.0Al–0.9Ni. In samples 91 and 92, the atomic ratio was 49.2Fe–42.0Ni–4.0Si–4.8Co. In samples 93 and 94, the atomic ratio was set at 50.0Fe–50.0Co. In samples 95 and 96, the atomic ratio was set at 49.0Fe–49.0Co–2.0V. In samples 97 and 98, the atomic ratio was set at 83.6Fe–4.4Co–12.0Si. In samples 99 and 100, the atomic ratio was set at 66.3Fe–7.4Co–16.4Si–9.9Al. The results are shown in Table 8A. It was confirmed that the thickness of the carbon-enriched portion in the examples shown in Table 8A was 8–12 nm. The comparative examples shown in Table 8A did not have a carbon-enriched portion.
[0196] Except for altering the composition (core composition) of the soft magnetic metal powder, samples 111-122 were performed in the same manner as samples 3 and 4. In samples 111 and 112, the atomic ratio was set to 81.6Fe–3.4Si–13.4B–1.6C. In samples 113 and 114, the atomic ratio was set to 63.2Fe–15.8Co–10.0B–5.0P–5.0Si–1.0Cr. In samples 115 and 116, the atomic ratio was set to 72.3Fe–18.2Si–9.5B. In samples 117 and 118, the atomic ratio was set to 56.0Fe–24.0Co–15.0P–5.0C. In samples 119 and 120, the atomic ratio was set to 56.0Fe–24.0Co–20.0B. In samples 121 and 122, the atomic ratio was set as 56.0Fe-24.0Co-15.0B-5.0Si. The results are shown in Table 8B. It was confirmed that the carbon-enriched portion thickness of the examples shown in Table 8B was 8–11 nm. The comparative examples shown in Table 8B did not have a carbon-enriched portion.
[0197] Except for changing the composition (core composition) of the soft magnetic metal powder, samples 131 to 136 were performed in the same manner as samples 5 and 6. In samples 131 and 132, the atomic ratio was set to 79.0Fe-1.0Si-10.0B-7.0Nb-3.0P. In samples 133 and 134, the atomic ratio was set to 63.2Fe-15.8Co-11.0B-9.0P-1.0Si. In samples 135 and 136, the atomic ratio was set to 63.2Fe-15.8Co-10.0B-5.0P-5.0Si-1.0Cr. The results are shown in Table 8C. It was confirmed that the carbon-enriched portion thickness of the examples shown in Table 8C was 9–11 nm. The comparative examples shown in Table 8C did not have a carbon-enriched portion.
[0198] Table 8A
[0199]
[0200] Table 8B
[0201]
[0202] Table 8C
[0203]
[0204] As shown in Tables 8A to 8C, the same results were obtained even when the composition of the soft magnetic metal powder was changed. In particular, the presence of Co in the soft magnetic metal powder easily increased the m value.
[0205] [Symbol Explanation]
[0206] 1: Soft magnetic metal particles
[0207] 2: Core
[0208] 10: Covering part
[0209] 11: Oxide Section
[0210] 12: Carbon enrichment section
[0211] 13: Coating section
[0212] 50: Mixture
[0213] 100: Powder coating device
[0214] 101: Rotor
[0215] 102: Pressure head.
Claims
1. A soft magnetic metal powder, wherein, Contains: soft magnetic metal particles with a core and a coating. The coating portion has a higher C concentration than the carbon-rich portion of the core portion.
2. The soft magnetic metal powder as described in claim 1, wherein, The coating portion has an oxide portion that is in contact with the surface of the core portion.
3. The soft magnetic metal powder as described in claim 1 or 2, wherein, Based on atomic number, the maximum concentration of C in the carbon-enriched section, C(LM), is more than 10 times the concentration of C, C(P), in the soft magnetic metal powder.
4. The soft magnetic metal powder as described in claim 1 or 2, wherein, The thickness of the carbon-enriched portion is 0.5 nm or more and 50.0 nm or less.
5. The soft magnetic metal powder as described in claim 1 or 2, wherein, The coating portion has a coating portion that contacts the surface of the carbon-enriched portion.
6. A magnetic core, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
7. A magnetic component, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
8. An electronic device, wherein, It comprises the soft magnetic metal powder according to any one of claims 1 to 5.
Citation Information
Patent Citations
Composite magnetic material, core using the same, and magnetic element
JP2004197218A
Complex magnetic material and method for manufacturing inductor using the same
JP2004363466A